Digital transformation and firm performance among Chinese manufacturing firms: A moderated-mediation model - Guangxia, Ma; Jaafar, Hartini (Asian Journal of Economic Modelling, 2025)
This paper examines how digital transformation (DT) influences the performance of Chinese manufacturing firms within the context of industrial upgrading. It considers both the short-term and long-term effects of DT and the mechanisms through which these effects unfold. Using panel data from A-share listed manufacturing firms between 2014 and 2023, the study develops a moderated mediation model in which resource allocation (RA) and innovation capability (INC) serve as mediators, while internal control (ICON) moderates the mediation paths. The findings reveal that DT has the most significant and apparent impact on firm performance, with a cumulative effect: the more intensive the DT efforts, the greater the benefits. RA exerts a direct influence on short-term performance (FPS), while INC plays a critical role in driving long-term performance (FPL). ICON demonstrates a two-pronged effect: it amplifies the efficiency impact of RA on FPS while constraining INC’s flexibility in the short term, but over time, it fosters FPL through innovation transformation. These findings suggest that firms can benefit most from DT when digital initiatives are aligned with governance and resource allocation and combined with efforts to build innovation capability. Such alignment not only translates short-term efficiency gains into immediate improvements but also ensures lasting competitiveness through sustained innovation.